Pengembangan Experiment Sheet Instalasi Penerangan Listrik Berbasis Problem Based Learning Kelas XI Jurusan TITL Di SMK Negeri 7 Surabaya - Mochammad Ardiansyah Sunarko; Joko Joko (Politeknik Kampar, 2024)
This research aims to produce a problem-based learning device for electrical lighting installation experiment sheet that is expected to provide solutions to teachers to improve student learning outcomes that are feasible to use. The feasibility refers to the aspects of validity, practicality, and effectiveness. This research method uses the Research and Development (R&D) method and for the development model used as a reference in this research, namely the 4-D model. Thiagarajan (1974: 5) states that there are four stages in the 4-D model, namely: (1) define which includes front-end-analysis (initial analysis), leaner analysis (learner analysis), task analysis (task analysis), concept analysis (concept analysis), and specifying instructional objectives (formulating learning objectives). (2) design, which includes the stages of contructing criterion-referenced tests, media selection, format selection, and initial design. (3) develope, which includes expert appraisal, and developmental testing. (4) disseminate which includes validating testing, packaging, and diffusion and adaptation which is the stage of product dissemination. The disseminate stage is carried out on a limited basis, namely by providing teaching materials developed to students in class XI TITL at SMK Negeri 7 Surabaya. The subjects of this study were students of class XI TITL 1 as a product trial, at SMK Negeri 7 Surabaya. This study uses a One-Group Pretest- Posttest Design research design to determine differences before and after in a group, by providing a treatment in the form of a problem-based learning-based electrical lighting installation experiment sheet, the achievement of student competence is obtained from whether there is an increase in grades before and after learning.